THE USE AND ECONOMIC VALUATION OF MANGROVE RESOURCE IN TONGKE-TONGKE MANGROVE AREA, SINJAI DISTRICT, SOUTH SULAWESI PROVINCE, INDONESIA - Suryawati Salam; Erni Indrawati; Andi Gusti Tantu; Andi Reski Puspita Ayu (Fish Scientiae, 2018)
The research was The aim of the research was to carry out to the economic valuation and the use of mangrove resource Tongke-Tongke at the mangrove area Sinjai District, South Sulawesi, Indonesia. Survey research approach was used in this research and data were analyzed descriptively and quantitatively. The result showed that mangroves were utilized to capture fisheries and wood sources utilization. The economic value of mangrove was $USD 4,330.95 /ha/year. Capture fisheries are the largest contribution, up to 94,47 percent, while mangrove wood utilization 5,53 percent to be a most important income source for society in coast who live in the vicinity. Therefore, coastal management policy was required to be developed by considering the impact on the socioeconomics of mangrove utilization on the community at area coast, especially related to coastal utilization area change.